Reconstructing Jerusalem : Persian period prophetic perspectives - Ristau, Kenneth A. (My University, 2016)
Jerusalem--one of the most contested sites in the world. Reconstructing Jerusalem takes readers back to a pivotal moment in its history when it lay ruined and abandoned and the glory of its ancient kings, David and Solomon, had faded. Why did this city not share the same fate as so many other conquered cities, destroyed and forever abandoned, never to be rebuilt? Why did Jerusalem, disgraced and humiliated, not suffer the fate of Babylon, Nineveh, or Persepolis? Reconstructing Jerusalem explores the interrelationship of the physical and intellectual processes leading to Jerusalem's restoration after its destruction in 587 B.C.E., stressing its symbolic importance and the power of the prophetic perspective in the preservation of the Judean nation and the critical transition from Yahwism to Judaism. Through texts and artifacts, including a unique, comprehensive investigation of the archaeological evidence, a startling story emerges: the visions of a small group of prophets not only inspired the rebuilding of a desolate city but also of a dispersed people. Archaeological, historical, and literary analysis converge to reveal the powerful elements of the story, a story of dispersion and destruction but also of re-creation and revitalization, a story about how compelling visions can change the fate of a people and the course of human history, a story of a community reborn to a barren city.
Keywords: Jerusalem; history